2017
DOI: 10.14814/phy2.13289
|View full text |Cite
|
Sign up to set email alerts
|

Neurocardiovascular deficits in the Q175 mouse model of Huntington's disease

Abstract: Cardiovascular dysautonomia as well as the deterioration of circadian rhythms are among the earliest detectable pathophysiological changes in individuals with Huntington's disease (HD). Preclinical research requires mouse models that recapitulate disease symptoms and the Q175 knock‐in model offers a number of advantages but potential autonomic dysfunction has not been explored. In this study, we sought to test the dual hypotheses that cardiovascular dysautonomia can be detected early in disease progression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 56 publications
(82 reference statements)
0
37
0
1
Order By: Relevance
“…It has been shown that dysfunction in the circadian regulation of autonomic outputs can be detected early in disease progression in the Q175 mice (Cutler et al, 2017). In the present study, we measured the impact of TRF on activity, CBT, HR, and HRV measured simultaneously in freely moving Q175 mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that dysfunction in the circadian regulation of autonomic outputs can be detected early in disease progression in the Q175 mice (Cutler et al, 2017). In the present study, we measured the impact of TRF on activity, CBT, HR, and HRV measured simultaneously in freely moving Q175 mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It reflects the dynamic balance of sympathetic and parasympathetic control of heart function, and displays a robust circadian rhythm. A prior study demonstrated that the Q175 mice exhibit a loss of circadian control in HRV day/night differences, as well as an overall decrease in HRV over a 24-h period when compared to WT controls (Cutler et al, 2017). It is worthwhile to note that a similar decrease in HRV has also been reported in HD patients beginning during the presymptomatic stage of disease progression (Andrich et al, 2002; Aziz et al, 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expanded CAG encodes a long poly‐glutamine (poly‐Q) sequence insertion in which mutant HTT aggregates form inclusion bodies that disrupt multiple cellular functions. Although deficits in skeletal muscle energy metabolism (Lodi et al., ), insulin sensitivity (Lalic et al., ), cardiovascular (Cutler et al., ), endocrine function (Aziz et al., ; Moffitt, McPhail, Woodman, Hobbs, & Bates, ), muscle strength (Busse, Hughes, Wiles, & Rosser, ), as well as weight loss (Aziz et al., ) all occur in HD, the most debilitating symptoms are associated with CNS dysfunction. These symptoms typically emerge in the fourth or fifth decade of life and progress until death 10 or 15 years later.…”
Section: Introductionmentioning
confidence: 99%